Arqueologia e turismo em São Cristóvão - Dantas, Angecila Maria da Conceição Silveira (2023)
This article aims to present a possible tourist-archaeological itinerary for the historic center of São Cristóvão. To this end, we understand archaeological tourism as a segment of cultural tourism, with good productivity and interaction between these two spheres, both for the cultural enjoyment of the property and for its preservation. Archaeological work carried out in the area of ??interest was used, in order to enrich the itineraries that are already practiced in tourism in general.